Infrastructure-FDI nexus in Nigeria: insights from nonlinear threshold regression model - Md. Mahmudul Haque; Mohammad Ashraful Ferdous Chowdhury; Mohammad Hassan Shakil; Mansur Masih (Inderscience Enterprises Ltd., 2021)
Infrastructural development of the host country is one of the major determinants of attracting FDI. However, the nonlinear threshold relationship between the infrastructural development and FDI inflow is yet to be explored. The objective of this research is to find the threshold effect of infrastructure on FDI in Nigeria. Using Hansen’s (2000) threshold regression over the period 1972–2015, the study found that the relationship between infrastructure development and FDI is nonlinear. Furthermore, the relationship between infrastructure and FDI is positive in both regimes; however, the marginal positive impact of infrastructural development in attracting FDI is more evident after the threshold level. The findings provide support to the regulators and policy makers to improve infrastructural development for attracting more FDI in the economy which can foster economic growth.